Depressive symptoms before and after long-term CPAP therapy in patients with sleep apnea - Gagnadoux, Frédéric; Le Vaillant, Marc; Goupil, François; Pigeanne, Thierry; Chollet, Sylvaine; Masson, Philippe; Bizieux-Thaminy, Acya; Humeau, Marie-Pierre; Meslier, Nicole (Chest, 2014)
The outcome of depressive symptoms under CPAP therapy for OSA-hypopnea syndrome (OSAHS) has been poorly evaluated. In this multicenter, prospective cohort study, we evaluated the prevalence and correlates of persistent depressive symptoms after long-term CPAP therapy for OSAHS. This study included 300 patients with OSAHS and depressive symptoms (13-item, self-rated Pichot depression scale [QD2A] ≥ 7) at diagnosis. The primary dependent variable was persistent depressive symptoms after ≥ 1 year of CPAP therapy. Multivariate regression analyses were performed to determine variables independently associated with the persistence of depressive symptoms. After an average of 529 days (range, 365-1,569 days) of CPAP therapy, the mean (SD) QD2A score decreased from 9.2 (2.0) to 5.4 (4.0) (P < .0001), but 125 patients (41.7%) presented persistent depressive symptoms. The persistence of depressive symptoms was independently associated with persistent excessive daytime sleepiness (EDS) (OR, 2.72; 95% CI, 1.33-5.61), comorbid cardiovascular disease (OR, 1.76; 95% CI, 1.02-3.00), and female sex (OR, 1.53; 95% CI, 1.09-2.13). A positive linear trend was observed for the adjusted OR of persistent depressive symptoms with decreasing CPAP effect on the Epworth sleepiness scale (P < .0001). CPAP therapy does not resolve depressive symptoms in many patients with OSAHS. Persistent depressive symptoms are strongly associated with EDS. Active monitoring of depressive symptoms is needed in patients with OSAHS who are treated with CPAP. Interventional trials are required to evaluate the impact of antidepressants, cognitive behavioral therapy, or both on comorbid depression in patients with OSAHS.